2013
DOI: 10.1002/pon.3451
|View full text |Cite
|
Sign up to set email alerts
|

Support needs and resources of sexual minority women with breast cancer

Abstract: SMW and their partners have many shared and unique support resources and barriers. Heteronormativity that is implicit in the structure of support resources can serve as a barrier to support for SMW and their partners. Flexibility in relationship roles enabling some SMW to include former partners as significant means of support may be a source of resiliency, particularly for unpartnered SMW cancer patients. Support needs and resources of SMW are best understood through an intersectionality framework that consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 24 publications
0
45
0
Order By: Relevance
“…Characteristics of support networks and the role and access to social support were the focus or components of 7 studies . Perceived social support varied widely across studies, with some patterns suggested.…”
Section: Resultsmentioning
confidence: 99%
“…Characteristics of support networks and the role and access to social support were the focus or components of 7 studies . Perceived social support varied widely across studies, with some patterns suggested.…”
Section: Resultsmentioning
confidence: 99%
“…Not only may a gay man feel vulnerable for disclosing this to his oncologist, but there may be no resources geared toward his sexual orientation. Lesbian women surviving breast cancer report traditional resources for women involving hair loss from chemotherapy and coping skills for dealing with partners are created for heterosexual women and these situations have different meanings within their community …”
Section: Introductionmentioning
confidence: 99%
“…Support groups have been shown to offer cancer patients significant emotional support (Paul et al, 2014;Gray, Fitch, Davis and Phillips, 1997;Helgeson, Cohen, Schukz and Yasko, 2000); in our analysis these groups were not always presented positively and discussions around BR between women who had made different choices were sometimes emotionally charged and problematic. This has implications for support group facilitators.…”
mentioning
confidence: 86%